Completeness of TNM staging of small-cell and non-small-cell lung cancer in the Danish cancer registry, 2004–2009 - Deleuran, Thomas (Dove Medical Press, 2012)
OBJECTIVE: We examined the completeness of TNM staging of small-cell (SCLC) and nonsmall- cell (NSCLC) lung cancer in the national Danish Cancer Registry (DCR) and whether staging varied by year of diagnosis, gender, age, degree of comorbidity, or presence of histopathological diagnosis. METHODS: We identified all patients with SCLCs and NSCLCs registered in the DCR during 2004–2009 and examined the completeness of their TNM registrations. Completeness was defined as the number of recorded individuals with TNM divided by the total number of patients. Completeness was calculated for TNM, T, N, and M individually, overall, and by year of diagnosis, gender, age at diagnosis, and comorbidity. Data regarding comorbidity was obtained from the Danish National Patient Register (DNPR). We performed separate analyses for patients with a histopathologically verified diagnosis of NSCLC. Finally, we designed an algorithm to categorize tumors with missing TNM components as limited, extensive, or distant disease. RESULTS: Overall TNM staging completeness was 77.5% (95% confidence interval (CI): 76.1%–78.8%) for SCLC and 77.9% (95% CI: 77.3%–78.4%) for NSCLC. Completeness did not vary by gender and increased during the study period. The proportion of staged patients was lower among patients above 80 years of age or with medium to high levels of comorbidity. CONCLUSION: Overall TNM completeness for SCLC and NSCLC in the Danish Cancer Registry is high, but decreases with increasing levels of comorbidity and at ages greater than 80 years. Researchers should be aware of these potential sources of bias.